Superiority of Cubic Perovskites Oxides with Strong B‐O Hybridization for Oxygen‐Anion Intercalation Pseudocapacitance. (11th May 2022) - Liang, Tingting; Zhang, Xiaqing; Su, Lijun; Hou, Ruilin; Yang, Bingjun; Lang, Junwei; Yang, Shengrong; Yan, Xingbin
Abstract: Perovskite materials can store charge through rapid oxygen anions intercalation. Although numerous perovskite materials owing to rich selections of A and B‐site elements are reported as electrodes of supercapatteries, the effect of the crystal structure of perovskite materials on their electrochemical performance has never been studied so far. Herein, using SrCo0.9 Mo0.1 O3− δ, SrFeO3− δ, Ba0.5 Sr0.5 Co0.8 Fe0.2 O3− δ, and LaMnO3− δ as research targets, it is proved that their corresponding cubic structure materials display the best electrochemical performance. And then, the origin of such superiority of cubic structure for SrCo0.9 Mo0.1 O3− δ is explored through experimental investigations and theoretical calculations. The results show that the increase in the content of oxygen vacancies and the enhancement of B‐O hybridization of cubic structure can optimize the electronic structure of the perovskite materials, thereby improving its conductivity and accelerating the reaction kinetics. The filtering strategy based on crystal structure proposed by this report will provide a new perspective to faster and more efficient choice of perovskite materials for supercapatteries. Abstract : It is found that cubic perovskite materials with strong B‐O hybridization are superior for oxygen anion intercalation pseudocapacitance using SrCo0.9 Mo0.1 O3− δ, SrFeO3− δ, Ba0.5 Sr0.5 Co0.8 Fe0.2O3− δ, and LaMnO3− δ as research targets. This is mainly because the increase in oxygen vacancies content and the enhancement of B‐O hybridization of cubic structure improve its conductivity and accelerate the reaction kinetics based on the research of SrCo0.9 Mo0.1 O3− δ .